Área de poliedros no cotidiano - Villas Boas, Fernando Cleber [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The study of this work is concentrated on the concept of area of polyhedra using planning. Initially we give the theoretical basis, then we present a sequence of activities that familiarize students with polyhedra, presenting examples of their daily lives, inducing them to identify theirs characteristics, teaching them to classify them, to relate the polyhedral surfaces to representations in the plan and to work the area concept of polyhedra through this relationship. To conclude we present problems situations in the daily lives, as application of this concept

O estudo deste trabalho está concentrado no conceito de área de poliedros utilizando planificações. Inicialmente damos o embasamento teórico, depois apresentamos uma sequência de atividades que familiariza os alunos com poliedros, apresentando exemplos do seu cotidiano, induzindo-os a identificar suas características, ensinando-os a classificá-los, a relacionar as superfícies poliedricas às suas representações no plano e trabalhar o conceito de área de poliedros através desta relação. Para finalizar apresentamos situações problemas do cotidiano, como aplicação deste conceito
Keywords: Matemática - Estudo e ensino; Geometria solida - Estudo e ensino; Poliedros; Matemática - Metodologia; Mathematics Study and teaching